Fuzhenghefuzhiyang Formula (FZHFZY) Improves Epidermal Differentiation via Suppression of the Akt/mTORC1/S6K1 Signalling Pathway in Psoriatic Models - Lu, Yue; Chen, Haiming; Zhang, Junhong; Tang, Bin; Zhang, Hongyu; Ma, Changju; Tang, Xiaojuan; Li, Li; Wu, Jingjing; Wei, Jianan; Li, Shaoping; Yang, Lei; et al. (Frontiers in Pharmacology, 2021)
Psoriasis is a chronic proliferative skin disorder characterised by abnormal epidermal differentiation. The Fuzhenghefuzhiyang (FZHFZY) formula created by Chuanjian Lu, a master of Chinese medicine in dermatology, has been external used in the Guangdong Provincial Hospital of Chinese Medicine for the treatment of psoriasis, but its mechanisms of action against psoriasis remain poorly understood. This study involved an exploration of the effects of FZHFZY on epidermal differentiation and its underlying mechanisms in interleukin (IL)-17A/IL-22/interferon (IFN)-γ/tumour necrosis factor (TNF)-α–stimulated HaCaT cells and in a mouse model of imiquimod (IMQ)-induced psoriasis. Cell viability was assessed by MTT assay. Epidermal differentiation was detected by reverse-transcription polymerase chain reaction and western blotting. Histological evaluation of the skin tissue was performed via haematoxylin and eosin staining, and the Akt/mTORC1/S6K1 pathway was analysed by western blotting. FZHFZY inhibited proliferation and improved epidermal differentiation in IL-17A/IL-22/IFN-γ/TNF-α–induced HaCaT cells. FZHFZY ameliorated symptoms of psoriasis, regulated epidermal differentiation and inhibited phosphorylation of the Akt/mTORC1/S6K1 pathway in the skin of mice with imiquimod-induced psoriasis. Our results suggest that FZHFZY may exhibit therapeutic action against psoriasis by regulating epidermal differentiation via inhibition of the Akt/mTORC1/S6K1 pathway.